Perbandingan Keberhasilan Terapi Antivirus Favipiravir dan Remdesivir pada Pasien Covid-19 di RSUD dr. Doris Sylvanus - Rhatna Dewi Riptasari; Abdul Rahem; Anita Purnamayanti (Jurnal Surya Medika (JSM), 2022)
All drugs used for COVID-19 therapy are circulated under a particular scheme, namely the Emergency Use Authorization (EUA) from the Food and Drug Administration. Considering that this COVID-19 is a new case, the high mortality rate, and the lack of research related to COVID-19 drug therapy in Central Kalimantan, a study was conducted to compare the success of COVID-19 treatment in severe patients using remdesivir and favipiravir antivirals with clinical evidence parameters. Number Needed To Treat (NNT) at the COVID-19 referral service at RSUD dr. According to inclusion, Doris Sylvanus in 140 study subjects was divided into 70 topics, each using favipiravir and remdesivir. The results of the study in the remdesivir group showed that 36 (51.43%) subjects recovered and 34 (48.57%) died, while in the favipiravir group, 48 (68.67%) recovered and 22 (31.43%) died. Calculation of the NNT parameter values for remdesivir was obtained with six results, indicating that it takes six COVID-19 patients to be treated with remdesivir to produce therapeutic success, at least one patient recovers. The ideal NNT value is number 1; the smaller the NNT value is close to 1, the more effective it is to produce the expected recovery or positive impact. On the other hand, the higher the NNT value, the lower the effectiveness.